2018
DOI: 10.1016/j.bbabio.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

State transitions in the cyanobacterium Synechococcus elongatus 7942 involve reversible quenching of the photosystem II core

Abstract: Cyanobacteria use chlorophyll and phycobiliproteins to harvest light. The resulting excitation energy is delivered to reaction centers (RCs), where photochemistry starts. The relative amounts of excitation energy arriving at the RCs of photosystem I (PSI) and II (PSII) depend on the spectral composition of the light. To balance the excitations in both photosystems, cyanobacteria perform state transitions to equilibrate the excitation energy. They go to state I if PSI is preferentially excited, for example afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
4
15
0
Order By: Relevance
“…Therefore, in our study, we characterized state transitions in S. elongatus and compared them to those in Synechocystis, which allowed us to obtain clearer conclusions. Our results confirm data demonstrating that a large amplitude of PSII fluorescence quenching is induced in State II in S. elongatus (Ranjbar Choubeh et al, 2018). This PSII quenching appears to be unrelated to spillover.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, in our study, we characterized state transitions in S. elongatus and compared them to those in Synechocystis, which allowed us to obtain clearer conclusions. Our results confirm data demonstrating that a large amplitude of PSII fluorescence quenching is induced in State II in S. elongatus (Ranjbar Choubeh et al, 2018). This PSII quenching appears to be unrelated to spillover.…”
Section: Introductionsupporting
confidence: 92%
“…However, more recent studies have questioned the definition of cyanobacterial state transitions as a rebalance of excitation energy arriving to one or another photosystem. The increase in fluorescence in State I has principally been associated with the functional detachment of PBS from the photosystems (Kaňa et al, 2009;Kaňa, 2013;Chukhutsina et al, 2015), whereas the decrease in fluorescence in State II was mainly attributed to a specific fluorescence quenching of PSII not involving spillover (Ranjbar Choubeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria allocate most of their chlorophyll a to photosystem I (PSI), whereas PBS are mostly coupled to photosystem II (PSII) (e.g., Myers et al 1980, Luimstra et al 2018. It has been hypothesized that PBS can dynamically move back and forth between PSII and PSI by state transitions (Mullineaux et al 1997, van Thor et al 1998), but recent research does not fully support this hypothesis (Chukhutsina et al 2015, Ranjbar Choubeh et al 2018, Calzadilla et al 2019. By contrast, the cyanobacterium Prochlorococcus, green algae, and many other eukaryotic phytoplankton (e.g., diatoms, coccolithophores, and dinoflagellates) lack PBS, but contain light-harvesting complexes consisting of chlorophylls and carotenoids that can effectively transfer light energy to both photosystems (Chisholm et al 1992, Natali and Croce 2015, Nawrocki et al 2016; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This is reminiscent of the situation in the cyanobacterium Synechococcus elongatus 7942 in which quenching of the PSII core was observed upon going from state I to state II. Also in that case spill-over could be ruled out because no such change in PSI emission was observed (Ranjbar Choubeh et al 2018). The most likely explanation for quenching of the PSII core is non-radiative energy dissipation within its reaction centre.…”
Section: Discussionmentioning
confidence: 99%
“…Time-resolved fluorescence of the cells was recorded at room temperature using a picosecond streak-camera system (van Stokkum et al 2008) as reported before (Bar Eyal et al 2017;Ranjbar Choubeh et al 2018), using a time window of 800 ps. The frequency-doubled output of a Ti:sapphire laser (Coherent, Mira) (800 nm) was used to excite the samples at 400 nm.…”
Section: Time-resolved Measurements and Data Analysismentioning
confidence: 99%